Chapter Microalgae: The Basis of Mankind Sustainability - María Fernández Sevilla, José (InTechOpen, 2017)
Microalgae were the basis of life into the planet, but only recently these microorganisms are exploited at a commercial scale. Thus, the production of pharmaceuticals, cosmetics, feed, and foods from microalgae is today a commercial reality increasing year by year. Additionally, microalgae have been proposed to be used to enhance the sustainability of existing industrial activities, as wastewater treatment and biofuel production. In this way, the utilization of microalgae at a large scale is considered a green revolution in the sustainability of mankind. This chapter is focused on reviewing the real contribution of microalgae to human activities. The last improvements of technologies and its uses, in addition to still existing bottlenecks for the massive exploitation of these microorganisms, are reviewed.